2009 International Conference on Energy and Environment Technology 2009
DOI: 10.1109/iceet.2009.512
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the performance of vermifilter at low temperature in winter

Abstract: The performance of the vermifilter in winter was investigated. The experimental results indicated that the temperature of vermifilter bed in winter was 1~5 higher than that of the ambient. However, the temperature was still a key factor for the vermifilter, low temperature could influence the activity of the earthworms. The filter bed temperature was positively correlated with the earthworm density. So was the unit-area biomass. Reversely, the filter bed temperature was negatively correlated with the density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Hence, to overcome the hindrance mentioned above to some extent and ensure the effective implementation of the VF technology, even in the colder climate, the researchers have adopted various innovative strategies to provide thermal insulation to the VFs, thereby protecting the micro‐environment inside the VF from the external freezing (Li et al, 2009; Yang et al, 2009; Yang et al, 2011; Yang & Zhao, 2008). For instance, Yang et al (2009) have introduced an elasticity plastic filler layer on the surface of the vermibed (schematically portrayed in Figure 2) to isolate the vermi‐ecosystem from the surroundings. The elasticity plastic filler layer acted as a barrier between the external environment and the vermibed media, eliminating their direct contact.…”
Section: Strategies To Trigger the Performance Of Vf Technologymentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, to overcome the hindrance mentioned above to some extent and ensure the effective implementation of the VF technology, even in the colder climate, the researchers have adopted various innovative strategies to provide thermal insulation to the VFs, thereby protecting the micro‐environment inside the VF from the external freezing (Li et al, 2009; Yang et al, 2009; Yang et al, 2011; Yang & Zhao, 2008). For instance, Yang et al (2009) have introduced an elasticity plastic filler layer on the surface of the vermibed (schematically portrayed in Figure 2) to isolate the vermi‐ecosystem from the surroundings. The elasticity plastic filler layer acted as a barrier between the external environment and the vermibed media, eliminating their direct contact.…”
Section: Strategies To Trigger the Performance Of Vf Technologymentioning
confidence: 99%
“…As a result, these earthworms get acclimatized very quickly to the wastewater treatment system, leading to the higher removal performance of the VFs (Binet et al, 1998) However, the application of this earthworm is beneficial only in the warmer climate since it flourishes at 15-25 C temperature . Furthermore, the studies indicated that the application of the E. fetida earthworms in colder regions resulted in a significant reduction in the nutrient and organic removal performance of the VFs (Arora & Kazmi, 2015;Yang et al, 2009).…”
Section: Selection Of Earthworm Species Optimization Of Earthworm Ino...mentioning
confidence: 99%
See 3 more Smart Citations